Tumour-draining axillary lymph nodes in patients with large and locally advanced breast cancers undergoing neoadjuvant chemotherapy (NAC): the crucial contribution of immune cells (effector, regulatory) and cytokines (TH1, TH2) to immune-mediated tumour cell death induced by NAC - Kaewkangsadan, Viriya; Verma, Chandan; Eremin, Jennifer M.; Cowley, Gerard P. (BioMed Central, 2016)
Background and Aim: The tumour microenvironment consists of malignant cells, stroma and immune cells. In women with large and locally advanced breast cancers (LLABCs) undergoing neoadjuvant chemotherapy (NAC), tumour-infiltrating lymphocytes (TILs), various subsets (effector, regulatory) and cytokines in the primary tumour play a key role in the induction of tumour cell death and a pathological complete response (pCR) with NAC. The contribution of the cellular and humoral responses to a pCR in nodal metastases, however, is poorly studied and was investigated.